Ethics and the built environment - Fox, Warwick (Professional ethics., 2000)
Much has been written in recent years on environmental ethics relating to the more general 'natural' environment but little specifically written about ethics of the built environment. Ethics and the Built Environment responds to this need and offers a debate on the ethical dimension of building in all its forms from a variety of disciplinary perspectives and approaches. This book should be of interest to architects, students of building and building design, environmentalists, politicians and general readers with an interest in ethics.